Review: Posed vs. Genuine Facial Emotion Recognition and Expression in Autism and Implications for Intervention - Webster, Paula J.; Wang, Shuo; Li, Xin (Frontiers in Psychology, 2021)
Impaired social interaction is one of the core characteristics of autism spectrum disorder (ASD). Social differences among ASD individuals often include their impairment in discerning other people’s emotions based on their facial expressions. In this review, we first cover the rich body of literature in studying deficits of facial emotion recognition (FER) in those with ASD including both behavioral studies and neurological findings. In particular, we highlight the class of subtle emotion recognition as well as various factors related to inconsistent findings in behavioral studies of FER in ASD. Then we discuss the dual problem of FER - namely facial emotion expression (FEE) or the production of facial expressions of emotion. Despite being less studied, social interaction involves both the ability to recognize emotions and to produce appropriate facial expressions. How facial expressions of emotion in those with ASD are perceived by others has remained an under-researched area. Finally, we propose a method for teaching FER/FEE (facial emotion teaching hierarchy [FETH]), which is based on recent research investigating FER/FEE in ASD with consideration for the use of posed vs. genuine emotions and static vs. dynamic stimuli. We also propose two possible teaching approaches: 1) a standard method of teaching progressively from simple drawings and cartoon characters to more complex audio-visual video clips of genuine human expressions of emotion with context clues or 2) teaching in a field of images that includes posed and genuine emotions to improve generalizability before progressing to more complex audio-visual stimuli. Lastly, we advocate for autism interventionists to use FER/FEE stimuli developed primarily for research purposes to facilitate the incorporation of well-controlled stimuli to teach FER and bridge the gap between intervention and research in this area.